Making the absent subject present in organizational research. (March 2016) - Driver, Michaela
This study explores how researchers engage with research subjects. Specifically, it examines the struggle to account for the lived experience of subjects under study while producing knowledge about and for them. Drawing on psychoanalytic, specifically Lacanian, theorizing, the study suggests that such struggles are even more complex when real subjects are absent and impossible to account for. It advances the idea that by articulating the research subject through four different discourses, researchers may take different positions toward this absence. In the first, researchers produce research subjects and put them to work. In the second, subjects are subsumed through systematic knowledge production. In the third, the subject serves the production of knowledge as a function of the split subject's enjoyment. In the fourth discourse the researcher becomes the object of desire so as to empower subjects in their becoming. It is suggested that each discourse allows researchers to take a different stance toward their research subjects. While discourses one and two are quite commonly adopted, discourses three and four may be alternatives for reflection that facilitate the creative expression of subjectivity, ethical choice and transformational, frame-breaking textual practices. Implications of this perspective for organizational research are discussed.